2013
DOI: 10.1111/cxo.12038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eye rubbing on the levels of protease, protease activity and cytokines in tears: relevance in keratoconus

Abstract: Background: Proteases, protease activity and inflammatory molecules in tears have been found to be relevant in the pathogenesis of keratoconus. We sought to determine the influence of eye rubbing on protease expression, protease activity and concentration of inflammatory molecules in tears. Methods: Basal tears were collected from normal volunteers before and after 60 seconds of experimental eye rubbing. The total amount of matrix metalloproteinase (MMP)-13 and inflammatory molecules interleukin (IL)-6 and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
156
0
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(174 citation statements)
references
References 63 publications
0
156
0
18
Order By: Relevance
“…Eye rubbing is a proven factor that triggers the onset and progression of the disease, through several effects including stimulation of inflammation. 112,113,119,120 Increasing evidence supports the fact that thinning and ectasia of the cornea are related to a degraded extracellular matrix involving inflammatory events (mainly increased levels of MMP-9, IL-6, and TNF-α) 10,[12][13][14]67,91 and increased oxidative stress. [143][144][145][146] However, the precise role of each of the identified molecular factors still needs to be defined in further studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye rubbing is a proven factor that triggers the onset and progression of the disease, through several effects including stimulation of inflammation. 112,113,119,120 Increasing evidence supports the fact that thinning and ectasia of the cornea are related to a degraded extracellular matrix involving inflammatory events (mainly increased levels of MMP-9, IL-6, and TNF-α) 10,[12][13][14]67,91 and increased oxidative stress. [143][144][145][146] However, the precise role of each of the identified molecular factors still needs to be defined in further studies.…”
Section: Resultsmentioning
confidence: 99%
“…All of these could probably be the result of a complex interaction of both genetic predisposition and environmental triggering factors, such as eye rubbing and contact lenses wear (the 'two-hit hypothesis') in keratoconus. 42,52,100,113,119,120 conditions in the cornea, will contribute to elucidate these questions and ultimately help to unravel the etiological mysteries of keratoconus. The tear film proteome has become and will stay as an area of high interest for the identification of potential targets for early diagnosis and therapy in these patients, due to its non-invasive nature.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical damage caused by microtraumas may affect Il-6 levels, increasing the risk of development of keratoconus. Balasubramanian et al [19] revealed a significant elevation in Il-6 concentrations after 60 seconds of eye rubbing by healthy volunteers. Confirmation of an aforementioned hypothesis may also be found in outcomes of a study conducted by Wilson et al [20] who revealed 2-40 times higher concentrations of proinflammatory cytokines, such as Il-6, in people using contact lenses.…”
Section: Discussionmentioning
confidence: 97%
“…Balasubramanian et al used specific enzymelinked immunosorbent assays to measure the amount of inflammatory markers 60 seconds after eye-rubbing in normal subjects. 51 They found an increased expression in tear matrix metalloproteinase-13, interleukin-6 and tumour necrosis factor-α in normal subjects. There was no significant change in collagenase activity.…”
Section: Pathological Changes Secondary To Eye Rubbing In Keratoconusmentioning
confidence: 96%
“…There was no significant change in collagenase activity. 51 These inflammatory changes after rubbing are thought to contribute to the pathogenesis.…”
Section: Pathological Changes Secondary To Eye Rubbing In Keratoconusmentioning
confidence: 99%